Analisis Laporan Keuangan Pemerintah Pusat Tahun 2005-2009 - , Sumarno; , Dr. Mamduh M. Hanafi, M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
One form of implementation of government accountability is the government's financial statement presentation. The financial statements consist of the statement of budget realization, balance sheet, statement of cash flow and notes to financial statements. The information presented in the general purpose financial statements is intended to fulfill information needs of all groups of users. As such the financial statements is not designed to fulfill any specific need from each respective user. However, not all users of government financial statements to understand the accounting that are tools to produce financial reports. Therefore, the required financial statement analysis to help users understand and interpret. Purpose of this study to analyze the Central Government Financial Report in 2005-2009, so as to help its users to take various decisions. Data used for analysis is the statement of budget realization and the balance sheet of central government for 2005-2009. The analytical method used is the financial ratio analysis, comparative analysis of financial statements, and common-size analysis. Based on financial ratio analysis found that the government's liquidity is good enough that shown by the average current ratio of 118%. The current ratio shows an increase which means that the government's ability to repay its shortterm obligations are heightened. The ratio of total debt to equity ratio shows a declining trend. Government revenues have a tendency to increase and the majority of tax revenues. Meanwhile, government expenditures also tended to increase. Central government expenditures were mainly used for purposes that are required and operationaly, that are for subsidies, employee expenditures and debt interest payments. Assets have increased, and the majority of assets are long-term investments and fixed assets. On the other hand, liability also increased with an average growth of only 6.09%, and most of the liabilities are long-term liabilities.